Augmentative releases of Diachasmimorpha longicaudata (Hymenoptera: Braconidae) for Ceratitis capitata (Diptera: Tephritidae) control in a fruit-growing region of Argentina - Sánchez, Guillermo (2016)
Field-open augmentative releases were conducted to assess the efficacy of Diachasmimorpha longicaudata (Ashmead) for the regulation of Ceratitis capitata (Weidemann) infesting Ficus carica (L.) in a commercial area located in a fruit-producing irrigated-valley of San Juan, central-western Argentina. Parasitoids were reared on Sensitive Lethal Temperature Vienna-8 strain of C. capitata at the BioPlanta San Juan facilities, and were weekly released throughout 9 weeks over two experimental plots of ca. 2.3 ha each with a density of 5200 wasps/plot. Host mortality and medfly emergence at the release plots were significantly 1.9-times higher and 1.5-times lower, respectively, than those recorded in the control plots. D. longicaudata females increase their effectiveness on medfly at both higher temperature (22–23 °C) and relative humidity (54–62%) values. Parasitoid females used in the study showed a good ability to spread once released in open-field. Between 16 and 75% of host mortality during the parasitoid release period was due to D. longicaudata, which appears to be promising for the control of medfly in San Juan as well as in other similar Argentinean fruit-growing semi-arid regions.